Quantum dot-based immunofluorescent imaging of Ki67 and identification of prognostic value in HER2-positive (non-luminal) breast cancer - Sun JZ (Dove Medical Press, 2014)
Jin-Zhong Sun,1,* Chuang Chen,1,* Guan Jiang,2 Wei-Qun Tian,3 Yan Li,4 Sheng-Rong Sun1 1Department of Breast and Thyroid Surgery, Renmin Hospital of Wuhan University, Wuhan, Hubei, People's Republic of China; 2Department of Dermatology, Renmin Hospital of Wuhan University, Wuhan, Hubei, People's Republic of China; 3Department of Biomedical Engineering, Wuhan University School of Basic Medical Sciences, Wuhan, Hubei, People's Republic of China; 4Department of Oncology, Zhongnan Hospital of Wuhan University and Hubei Key Laboratory of Tumor Biological Behaviors and Hubei Cancer Clinical Study Center, Wuchang District, Wuhan, Hubei, People's Republic of China *These authors contributed equally to this work Background: The immunohistochemical assessment of Ki67 antigen (Ki67) is the most widely practiced measurement of breast cancer cell proliferation; however, it has some disadvantages and thus the prognostic value of Ki67 in breast cancer remains controversial. Our previous studies confirmed the advantages of quantum dots-based nanotechnology for quantitative analysis of biomarkers compared with conventional immunohistochemistry (IHC). This study was designed to assess Ki67 by quantum dot-immunohistochemistry (QD-IHC) and investigate the prognostic value of the Ki67 score in human epidermal growth factor receptor 2 (HER2)-positive (non-luminal) breast cancer. Methods: Ki67 expression in 108 HER2-positive (non-luminal) breast cancer specimens was detected by IHC and QD-IHC. Two observers assessed the Ki67 score independently and comparisons between the two methods were made. The prognostic value of the Ki67 score for five-year disease-free survival was estimated. Results: The same antigen localization, high correlation of staining rates (r=0.993), and high agreement of measurements (Κ=0.874) of Ki67 expression (cutoff: 30%) in breast cancer were found by QD-IHC and conventional IHC. The QD-IHC had a better interobserver agreement for the Ki67 score than conventional IHC (t=-7.280, P<0.01). High Ki67 expression (cutoff: 30%) was associated with shorter disease-free survival (log-rank test; IHC, P=0.026; QD-IHC, P=0.001), especially in the lymph node-negative subgroups (log-rank test; IHC, P=0.017; QD-IHC, P=0.002). Conclusion: QD-IHC imaging of Ki67 was an easier and more accurate method for detecting and assessing Ki67. The Ki67 score was an independent prognosticator in the HER2-positive (non-luminal) breast cancer patients. Keywords: quantum dots, breast cancer, Ki67, disease-free survival, prognosis